Biological reactions to metal particles and ions in the synovial layer of mice - Cheng, Xiangyun; Dirmeier, Sabine C.; Haßelt, Sandra; Baur-Melnyk, Andrea; Kretzer, Jan Philippe; Bader, Rainer; Utzschneider, Sandra; Paulus, Alexander C. (Materials, 2020)
Metal particles and ions released from implants not only have a fundamental effect on the longevity of total joint replacements, but can also be disseminated to remote organs. Periprosthetic tissues harvested during revision surgeries mainly reflect end-stage failure but may not adequately reveal initial biological reactions and systemic side effects. Therefore, primary reactions caused by metal particles and ions were investigated in an established murine model. Left knee joints in three groups, each consisting of ten female BALB/c mice, received injections of metal ions (MI), metal particles (MP) and phosphate-buffered saline (PBS) (control). Seven days after the injection, immunohistochemical analyses of the synovial layer were performed with respect to some biological markers including Tumor necrosis factor -α (TNF-α), Interleukin-6 (IL-6), Interleukin-1β (IL-1β), Cluster of Differentiation 45 (CD45), Cluster of Differentiation 68 (CD68) and Cluster of Differentiation 3(CD3). The MP group showed significantly enhanced proinflammatory cytokine expression (TNF-α, IL-6 and IL-1β) compared with the other groups (p < 0.05). Interestingly, CD3, as a marker for T lymphocytes, did not increase in any of the groups. The MI group showed a significantly increased expression of CD45 compared with the control group (p < 0.05). Therefore, during the primary process, metal particles have stronger pro-inflammatory potential than metal ions, and T lymphocytes did not seem to be activated in our murine model. Systemic reactions caused by metal particles and ions were found by observing the untreated right knees.
Gesehen am 16.12.2020